Alternativas transfusionales, empleadas en pacientes con anemias hemolíticas mediante la realización de pruebas antiglobulínicas y protocolos de tipificación sanguínea de usuarios atendidos en el servicio de medicina transfusional del hospital provincial general docente de riobamba, durante el periodo diciembre 2013 mayo 2014. - Ramón Tillaguango, Jaime Fabricio (2015)
This research work is done in the Department of Transfusion Medicine General Teaching Hospital, with the completion of antiglobulínicas tests and protocols typing with the aim of assessing transfusion alternatives in patients with hemolytic anemias, testing Coombs have objectively identify the presence or agglutinins antibody reagents with RBCs os, generating hemolytic reaction and the reduction in concentration of hemoglobin. Blood transfusion is a procedure risk is sought with conducting compatibility tests the longer life of red blood cells transfused generating a minimal expression of reaction, the present research work is supported with a source of bibliographical consultation, methodology study the scientific method as it is a process to explain phenomena, establishing relationships between the facts and state laws that explain the phenomena to obtain a result, the population studied is 40 leukoreduced blood transfused patients, it lacks antibodies and expressions leukocyte concentration, post transfusion valuation is performed by applying on patients' direct Coombs test, negative results respond favorably to the hypothesis, the conclusion of this work, antiglobulin test or indirect Coombs was identified in the samples studied the presence of antibody associated with hemolytic clinical use of packed red blood cells leucoreduced as transfusional alternative to prevent further complications in transfusion associated with leukocytes, platelets and plasma containing a high antigenicity is recommended, for each transfusion these clinical cases blood seek lacking antigens assessed with compatibility testing and post transfusional Control post transfusional.